Scenario of Mathematic Learning Based on Bruner at School - Suprapto Manurung (Bandar Lampung University (UBL), 2013)
This study attempts to discuss the scenario of learning by BUNER’s theory at school. In designing the Lesson Plan of Learning, the teachers often confused to make an interesting and students actively. However, Lesson Plan (Scenario Learning) is a very important element to succeed the goal of learning. In this research, the writer used Bruner’s theory of learning to help the teacher in designing the activities of teaching and learning process. Bruner’s theory of Learning is based on four activities as below: (1) Construction, (2) Notation, (3) Contrast, (4) Connectivity. According to Bruner’s theory, successful learning is the process of teaching which oriented with the concept and the structure in the process of learning related to the four activities which has been discussed in the previous statement